(untitled) (Marketing Journal, 2025)
This article analyzes the issues of ensuring the external economic security of the national economy in the context of global economic trends and risks. The study examines indicators of external economic security, global risk factors, and approaches aimed a t strengthening economic stability. Using the example of Uzbekistanʼs economy, the analysis is carried out based on such indicators as export diversification, currency security, balance of payments, and external debt stability. The results show that, under conditions of global economic volatility, ensuring the external economic security of the national economy requires comprehensive strategic measures. 379